Indentation-induced plastic behaviour of nanotwinned Cu/high entropy alloy FeCoCrNi nanolaminate: an atomic simulation. Issue 16 (2nd March 2020) - Feng, Hui; Tang, Jingwen; Chen, Haotian; Tian, Yuanyuan; Fang, Qihong; Li, Jia; Liu, Feng
Abstract : Using large-scale molecular dynamics (MD) simulations, the effects of interface and layer number in the nanoindentation response of experimentally observed nanotwinned Cu/high entropy alloy (HEA) FeCoCrNi nanolaminate are studied. Abstract : Using large-scale molecular dynamics (MD) simulations, the effects of interface and layer number in the nanoindentation response of experimentally observed nanotwinned Cu/high entropy alloy (HEA) FeCoCrNi nanolaminate are studied. The dislocations are nucleated and emitted, which are more limited to the first twinning layer > second twinning layer > HEA layer. The stacking fault strengthening is pronounced due to the obvious difference of stacking fault energy between Cu and HEA, which can be rarely observed from the previous work in traditional alloys and metals. After the indentation induced deformation, the nanotwinned Cu/HEA FeCoCrNi nanolaminates for different layer numbers generate a mass of Shockley partial dislocations to cause the good plasticity, attributed to the strong strain gradient effect. The strong layer number and interface structure effects found here can provide insight for the design of advanced nanolaminate with high strength and good plasticity.